Association of physical activity with risk of metabolic syndrome: findings from a cross-sectional study conducted in rural area, Nantong, China. Issue 19 (1st October 2016) - Xiao, Jing; Wu, Chuanli; Xu, Guangfei; Huang, Jianping; Gao, Yuexia; Lu, Qingyun; Hua, Tianqi; Cai, Hui
ABSTRACT: The prevalence of metabolic syndrome increases rapidly worldwide, and its association with physical activity (PA) varies with race and lifestyles. Little is known about the association in rural China. The Nantong Metabolic Syndrome Study recruited 13, 505 female and 6997 male participants in 2007 and 2008. Socio-demographic characteristics, and physiological and behavioural data were collected. Logistic regression model was applied to estimate associations of metabolic syndrome and its components with different PAs. The overall metabolic syndrome prevalence was 21.6% in current study. Increasing total PA or moderate-to-vigorous-intensity occupational PA was associated with decreasing 5%–60% risk of having metabolic syndrome and abnormal metabolic syndrome components in both genders. An association between leisure-time PA and blood pressure was found in men, but no associations between leisure-time PA and metabolic syndrome components were found in women. Commuting PA, such as walking and taking bus, by bicycle and walking only, was associated with decrease of 20%–45% risk of several abnormal metabolic syndrome components in women. This study provides information for future investigation into the nature of these associations so that recommendations can be developed to reduce the prevalence of metabolic syndrome and its components among rural population in China.